Classroom Techniques To Develop Students English Reading Skills: A Naturalistic Study At Smp Negeri 22 Surakarta - Damayanti, Fety, Prof. Dr. Endang Fauziati, M. Hum (2017)
This research is aimed to describe the types of classroom techniques used by the teacher, the purpose of every classroom technique, teachers' roles, students' roles, and role of instructional material to develop students' English reading skills at SMP Negeri 22 Surakarta. The type of this research is descriptive qualitative research especially naturalistic study. The method of collecting data in this study is interview, observation, and document. The result of the research showed that there are several classroom techniques used by English teacher at SMP Negeri 22 Surakarta such as: reading aloud, translating sentence, silent reading, and question and answer. There are several classroom techniques used by the teacher and each classroom technique has purpose. Reading aloud is to improve pronunciation of the student and to practice fluency in reading of the student. Translating sentence is to help the students to know the meaning of sentence. Silent reading is to help the students more concentrate to comprehend the text easily. Question and answer are to make the student more active in the class and to know how the students' comprehension of the text. The teacher has roles as planner, manager, controller, facilitator, motivator, and explainer. The students have some roles such as subject learning, object learning, monitor and evaluator of his or her own progress, learners learn from the teacher, from the other students and other teaching sources, tutor of others learners and a member of a group and learn by interacting with others. There are some materials used by English teacher, such as: book, textbook, dictionary, another source from internet as additional material. The roles of instructional materials are as a resource for presentation materials (spoken or written), as a reference source for learners on grammar, vocabulary, pronunciation, and so on, and a source of stimulation and ideas for classroom activities. The writer concludes that English teachers at SMP Negeri 22 Surakarta used some classroom techniques to develop students' English reading skills. Some classroom techniques can make the students more interested when teaching reading process.